2007
DOI: 10.1529/biophysj.106.092734
|View full text |Cite
|
Sign up to set email alerts
|

Guard Cells Elongate: Relationship of Volume and Surface Area during Stomatal Movement

Abstract: Stomata in the epidermis of photosynthetically active plant organs are formed by pairs of guard cells, which create a pore, to facilitate CO2 and water exchange with the environment. To control this gas exchange, guard cells actively change their volume and, consequently, surface area to alter the aperture of the stomatal pore. Due to the limited elasticity of the plasma membrane, such changes in surface area require an exocytic addition or endocytic retrieval of membrane during stomatal movement. Using confoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 18 publications
5
76
0
Order By: Relevance
“…8 Furthermore, GFP-mTn-expressing guard cells displayed heavily bundled actin microfilaments and their stomatal opening was suppressed during the diurnal cycles. 8 Three-dimensional morphometrical analysis further showed that guard cells elongated when stomata opened, 26 thus also clearly demonstrating the importance of dynamic actin bundling in guard cell elongation. Indeed, the involvement of actin dynamics during guard cell movement has been suggested through various pharmacological, imaging and molecular genetic studies (for details see the excellent review by Galatis and Apostolakos (2004)).…”
Section: Actin Bundling and Stomatal Opening: Our Hypothesesmentioning
confidence: 95%
“…8 Furthermore, GFP-mTn-expressing guard cells displayed heavily bundled actin microfilaments and their stomatal opening was suppressed during the diurnal cycles. 8 Three-dimensional morphometrical analysis further showed that guard cells elongated when stomata opened, 26 thus also clearly demonstrating the importance of dynamic actin bundling in guard cell elongation. Indeed, the involvement of actin dynamics during guard cell movement has been suggested through various pharmacological, imaging and molecular genetic studies (for details see the excellent review by Galatis and Apostolakos (2004)).…”
Section: Actin Bundling and Stomatal Opening: Our Hypothesesmentioning
confidence: 95%
“…Polarized light microscopy and field emission scanning electron microscopy have revealed that cellulose microfibrils are arranged radially relative to the stomatal pore in mature guard cells so as to constrain radial cell expansion (Palevitz and Hepler, 1976;Fujita and Wasteneys, 2014), instead favoring longitudinal cell expansion during stomatal opening (Wu et al, 1985;Meckel et al, 2007). However, fundamental questions remain to be addressed, such as whether there are any differences in cellulose organization between open and closed stomatal guard cells, and if so, how cellulose reorientation and/or reorganization facilitate stomatal movements.…”
mentioning
confidence: 99%
“…1 Cellulose in guard cells is arranged radially, 11,12 and xyloglucan is a hemicellulose that modulates wall mechanics 13 and is present in guard cell walls. 4 To test whether cellulose and xyloglucan regulate the anisotropic deformation of guard cells during stomatal movements, 14,15 we analyzed mutants deficient in cellulose or lacking detectable xyloglucan, finding that cellulose restricts, whereas xyloglucan facilitates longitudinal expansion and contraction in guard cells, thus regulating stomatal aperture. 1 Cellulose and xyloglucan are also required for the reorganization of cellulose in guard cells between a diffuse pattern in the open state and extensive bundles in the close state.…”
Section: Cellulose and Xyloglucan Regulate Anisotropic Guard Cell Expmentioning
confidence: 99%
“…2) that integrates several aspects of guard cell geometry and dynamics, including aperture, 1 pore area, surface area, and volume changes. 15,25 In this model, the guard cell pair is constructed with anisotropic shell elements, including mechanical interactions with neighboring cells. This model enables quantitative investigation of changes in turgor and of interactions between guard cells and surrounding cells during stomatal movements.…”
Section: Automated Detection Of Mts and Cscs Using Image Analysismentioning
confidence: 99%